Obsolescence Challenges for Product-Service Systems in Aerospace and Defence Industry - Romero Rojo, Francisco Javier; Roy, Rajkumar; Shehab, Essam; Wardle, P. J. (Cranfield University Press, 2009)
The aerospace and defence industries are moving towards new types of agreement such as availability contracts based on Product-Service System (PSS) business models. Obsolescence has become one of the main problems that will impact on many areas of the system during its life cycle. This paper presents the major challenges to managing obsolescence for availability contracts, identified by means of a comprehensive literature review and several interviews and forums with experts in obsolescence management. It is observed that there is a lack of understanding of the impact of obsolescence on whole life cost. Experts agree that the development of a framework to support estimation, management, and mitigation of these costs is desirable, but the difficulty in forecasting future obsolescence issues constrains industry to a reactive approach rather than proactive.
Organised by: Cranfield University
Keywords: Obsolescence Management; Obsolescence Costing; Product Service Systems